Individual Differences in Gelotophobia Predict Responses to Joy and Contempt. (13th April 2015) - Hofmann, Jennifer; Platt, Tracey; Ruch, Willibald; Proyer, René T.
In a paradigm facilitating smile misattribution, facial responses and ratings to contempt and joy were investigated in individuals with or without gelotophobia (fear of being laughed at). Participants from two independent samples ( N 1 = 83, N 2 = 50) rated the intensity of eight emotions in 16 photos depicting joy, contempt, and different smiles. Facial responses were coded by the Facial Action Coding System in the second study. Compared with non-fearful individuals, gelotophobes rated joy smiles as less joyful and more contemptuous. Moreover, gelotophobes showed less facial joy and more contempt markers. The contempt ratings were comparable between the two groups. Looking at the photos of smiles lifted the positive mood of non-gelotophobes, whereas gelotophobes did not experience an increase. We hypothesize that the interpretation bias of "joyful faces hiding evil minds" (i.e., being also contemptuous) and exhibiting less joy facially may complicate social interactions for gelotophobes and serve as a maintaining factor of gelotophobia.